USING BINGO GAME AND THEIR EFFECT ON GRADE EIGHT STUDENTS’ VOCABULARY ACQUISITION AT SMP AL –QUR’AN MA’RIFATUSSALAAM SUBANG - Abdillah NA (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2017)
This research entitle “Using Bingo Game and Their Effect on Grade Eight Students’ Vocabulary Acquisition at SMP Al–Qur’an Ma’rifatussalaam Subang” principally aims to investigate whether or not there is significant effect of using bingo game on vocabulary acquisition. The research methodology adopted was quasi-experiment method, with the research design being Randomize posttest only design. The research samples were taken using cluster random sampling, with total number of sample being 86 students. The location of this research was SMP Al-Qur’an Ma’rifatussalaam Subang. To collect data, the writer will prepare instrument in form of multiple choice that consist of 60 questions that will be tried out. The result of try out is chosen 30 of question item and will be post-test sample class that will be given to students after the treatment. The research data were analyzed Normality and Homogeneity test. The findings indicate that there was significant effect of post-test score between the students who received using bingo game and students who did not receive using bingo game. It can be seen from the data analysis using ANOVA that showed Fobserved (5.202) is higher than Ftable (4.02). it means that using bingo game has significant effect on students’ vocabulary acquisition.